2021
DOI: 10.3389/fpsyg.2021.643395
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy or Psychological Outcomes of Psychotherapy Interventions for Infertility: A Meta-Analysis

Abstract: Background: The pregnancy and psychological status of infertile couples has always been a concern, but there is no clear evidence for the efficacy of psychotherapy for infertile couples. This study aimed to summarize the current evidence of the effects of psychotherapy on psychological and pregnancy outcomes for infertile couples.Method: We searched Ovid MEDLINE, Ovid EMbase, The Cochrane Library, and Web of Science (ISI) for articles published from 1946 to June 26, 2020. The pregnancy outcomes, psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
(77 reference statements)
1
11
0
2
Order By: Relevance
“…Currently, the more common intervention technologies include preimplantation genetic testing, IVF-ET, intracytoplasmic sperm injection (ICSI), and cryopreservation of embryos [ 26 ]. With the advancement of science, this technology has been continuously developed, and the clinical pregnancy rate of infertile patients has been greatly improved [ 27 ]. However, in the process, it was found that a large number of patients still could not obtain clinical pregnancy after receiving high-quality embryo transfer for many times, that is, repeated implantation failure (RIF) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the more common intervention technologies include preimplantation genetic testing, IVF-ET, intracytoplasmic sperm injection (ICSI), and cryopreservation of embryos [ 26 ]. With the advancement of science, this technology has been continuously developed, and the clinical pregnancy rate of infertile patients has been greatly improved [ 27 ]. However, in the process, it was found that a large number of patients still could not obtain clinical pregnancy after receiving high-quality embryo transfer for many times, that is, repeated implantation failure (RIF) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the interventions that has enjoyed significant positive results in reducing distress caused by infertility is cognitive-behavioral therapy (CBT). Numerous studies have suggested that CBT techniques are useful in managing perceived stress and infertility-related mood disorders (such as anxiety) (Zhou, Cao, Liu, & Xiao, 2021). Such techniques include relaxation methods (autogenic training, progressive relaxation), stress inoculation training (SIT), cognitive restructuring (techniques for identifying and modifying distorted cognitions induced by automatic thoughts about infertility; e.g.…”
Section: Psychological Intervention Strategies For Patients With Infertility -Opportunities and Challengesmentioning
confidence: 99%
“…It has been over two decades that Cognitive Behavioral Therapy (CBT) has been widely introduced for the treatment of anxiety and depression related to infertility [ [14] , [15] , [16] , [17] ]. Although evidence has confirmed the effectiveness of CBT on the improvement of psychological problems of infertile women, there is limited access to CBT therapists [ 16 , [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%